Educational video games in a cultural perspective on the example of the series “Komputerowa Gratka 3D” - Krakowiak, Anna (Replay. The Polish Journal of Game Studies, 2023)
The article is an attempt to analyze a hitherto undescribed series of educational digital games for children „Komputerowa Gratka 3D” (Egmont Polska 2006– 2010) in terms of their cultural functions. For this purpose, the author adapts the methodology of new media studies in pedagogical sciences formulated by Janusz Gajda to the subject of games studies. She reflects on four selected titles in chronological order: Magiczna kula Papatki (2006), Przygoda w piramidzie (2007), Porwanie Łakomczucha (2008), Zaczarowana księga (2010). The conclusion reveals the predominant presence of the ludic and dissemination function of a variety of content, with positive and negative aspects.